Mathematical Thinking Process of Gifted Elementary School Students in Tasikmalaya City: A Case Study - Hetty Patmawati; Een Unaenah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
This study aims to describe the mathematical thinking process of gifted elementary school students in Tasikmalaya City in solving mathematical problems that include aspects of conceptual understanding, reasoning, problem solving, representation and mathematical connections. Data were collected through mathematical tests with five higher order thinking skill (HOTS) items, clinical interviews, and direct observations. Scoring reliability between two independent raters showed a high level of agreement (κ = 0.82). Data were analyzed qualitatively through data reduction, categorization, triangulation, and interpretation of emerging patterns. The subjects of the study were ten gifted students identified based on high mathematical ability scores in elementary schools in Tasikmalaya City. Data analysis used a qualitative approach with a case study design through the stages of data reduction to sort out relevant information, data presentation in the form of descriptions and categorization, data triangulation to validate findings from various sources, and drawing conclusions based on patterns that emerge from the data. The findings reveal that gifted students display time efficiency, multiple strategies, and reflective checking behavior in mathematical problem-solving. Of the ten students, one was in the very high category, seven were in the high category, and two were in the medium category. The most dominant indicators were mathematical reasoning and connections, while representation and conceptual understanding showed greater variation. Of the ten students, one student is in the very high category, seven students are in the high category, and two students are in the medium category. Each indicator implies targeted educational support: enrichment tasks for conceptual understanding, structured argumentation exercises for reasoning, open-ended and real-world tasks for problem solving, visual and model-based scaffolding for representation, and interdisciplinary activities for mathematical connections. These findings underscore the need for differentiated, problem-based, and creativity-oriented learning approaches to optimize the potential of gifted students in elementary schools.